2017
DOI: 10.3892/etm.2017.4984
|View full text |Cite
|
Sign up to set email alerts
|

Warm sparse-dense wave inhibits cartilage degradation in papain-induced osteoarthritis through the mitogen-activated protein kinase signaling pathway

Abstract: Cartilage degradation is an important in the pathogenesis of osteoarthritis (OA). Abnormal activation of the mitogen-activated protein kinase (MAPK) signaling pathway in chondrocytes promotes an inflammatory response, resulting in the release of chondral matrix-degrading enzymes that accelerate the degradation of cartilage. As a non-pharmaceutical and non-invasive physical therapy regimen, warm sparse-dense wave (WSDW) has been successfully used for the treatment of OA. However, it remains unclear whether WSDW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For example, the PI3K/Akt pathway regulates the activation of T and B lymphocytes. 27 In addition, both the expression and phosphorylation levels of Akt are higher in LN than those in healthy donors, in favor of an upregulation of PI3K and mTOR activity. 28 Similarly, in terms of IgA patients, the PI3K-Akt-mTOR pathway is activated in their podocytes, which can reduce the level of autophagy in podocytes and lead to podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the PI3K/Akt pathway regulates the activation of T and B lymphocytes. 27 In addition, both the expression and phosphorylation levels of Akt are higher in LN than those in healthy donors, in favor of an upregulation of PI3K and mTOR activity. 28 Similarly, in terms of IgA patients, the PI3K-Akt-mTOR pathway is activated in their podocytes, which can reduce the level of autophagy in podocytes and lead to podocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that the PI3K/AKT pathway that involves AKT1 prevents chondrocyte apoptosis [58]. TP53 inhibits DNA replication, induces apoptosis, and accelerates cartilage degradation [59]. In addition, researchers have demonstrated that the VEGFA is closely associated with many pathological responses, such as osteophyte formation and cartilage degeneration in OA [60].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the HSP90 protein can improve cartilage degeneration and prevent the development of OA. [ 40 ] TP53 is an important tumor suppressor gene. The encoded protein P53, which regulates the cell cycle, DNA repair, apoptosis, and signal transduction, is a main factor involved in cell stress reactions.…”
Section: Discussionmentioning
confidence: 99%